2020
DOI: 10.1007/s00535-020-01695-7
|View full text |Cite|
|
Sign up to set email alerts
|

Retinoic acid receptor γ activation promotes differentiation of human induced pluripotent stem cells into esophageal epithelium

Abstract: Background The esophagus is known to be derived from the foregut. However, the mechanisms regulating this process remain unclear. In particular, the details of the human esophagus itself have been poorly researched. In this decade, studies using human induced pluripotent stem cells (hiPSCs) have proven powerful tools for clarifying the developmental biology of various human organs. Several studies using hiPSCs have demonstrated that retinoic acid (RA) signaling promotes the differentiation of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 40 publications
(89 reference statements)
0
10
0
Order By: Relevance
“…Alisol B (purity > 97%) was extracted and purified, and the structure was confirmed by comparing the 1 H, 13 C NMR, and MS data with reported data [29]. Dried rhizomes of Alisma orientale were extracted three times with 95% ethanol and then concentrated under vacuum to yield a crude extract, which was suspended in H 2 O followed by partition with AcOEt.…”
Section: Extraction Of Alisol B From Alisma Orientalis (Sam)mentioning
confidence: 99%
See 1 more Smart Citation
“…Alisol B (purity > 97%) was extracted and purified, and the structure was confirmed by comparing the 1 H, 13 C NMR, and MS data with reported data [29]. Dried rhizomes of Alisma orientale were extracted three times with 95% ethanol and then concentrated under vacuum to yield a crude extract, which was suspended in H 2 O followed by partition with AcOEt.…”
Section: Extraction Of Alisol B From Alisma Orientalis (Sam)mentioning
confidence: 99%
“…Retinoic acid receptors (RARs), composed of three subtypes (RARα, RARβ, and RARγ), belong to the steroid/thyroid superfamily of nuclear hormone receptors. RARα is expressed in most tissues, whereas RARβ is mainly expressed in central nervous system [12] and RARγ is mainly expressed in skin, epithelium, and cartilage [13]. RARs are activated by the biologically active metabolite of retinol such as all-trans retinoic acid (atRA) and 9-cis retinoic acid [14], and form heterodimers with retinoid X receptor (RXR) to regulate gene transcription and signal transduction pathways.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the present study demonstrated the involvement of Zfp750 in the esophageal keratinocyte differentiation program through the upregulation and downregulation of Zfp750 expression with chemical stimulation and inhibition, by ATRA and Compound E, respectively, of the differentiation program in mNEEOs. ATRA is a chemical promoter of keratinocyte differentiation in esophageal cells (28,29) and was used in the present study to induce the epithelial differentiation program. Alternatively, γ-secretase inhibitor Compound E was used to mimic the inhibition of the keratinocyte differentiation program through the inhibition of the NOTCH signaling pathway (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…RNA was extracted as aforementioned from the ATRA-treated cells at 48 h post-treatment and subjected to RT-qPCR analysis. Experiments were performed on KYSE30 and KYSE180 cell lines using previously reported ATRA concentrations as a reference to determine the optimal ATRA concentration for each cell line (28).…”
Section: Chemically Induced Manipulation Of Mneeo Differentiationmentioning
confidence: 99%
“…The scarcity of specimens of human embryo and fetal organs has hindered studies on human developmental biology. In previous decades, various organs and tissues derived from the endoderm, mesoderm, and ectoderm have become able to be induced from human pluripotent stem cells, such as human embryonic stem cells (hESCs) and human induced pluripotent stem cells (hiPSCs) (Koterazawa et al, 2020;Shi et al, 2017;Suzuki et al, 2019), which has allowed us to investigate normal and pathological human developmental processes and their underlying mechanisms. McCracken et al reported the generation of human pluripotent stem cell-derived gastric organoids (hGOs); however, the hGOs lacked subepithelial SM tissue (McCracken et al, 2014).…”
Section: Introductionmentioning
confidence: 99%